1997
DOI: 10.1073/pnas.94.5.1955
|View full text |Cite
|
Sign up to set email alerts
|

Peptide inhibition of glomerular deposition of an anti-DNA antibody

Abstract: Antibodies to double-stranded DNA are pathognomonic of systemic lupus erythematosus and deposit in the kidneys of lupus patients to cause glomerulonephritis. Recent data suggest that a significant proportion of anti-DNA antibodies may cross-react with renal antigens and be sequestered in the kidney by virtue of this cross-reactivity. If this is true, antigenic competition for pathogenic antibodies might prevent their deposition in kidneys and the ensuing tissue damage. To generate surrogate antigens that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 24 publications
(23 reference statements)
4
142
0
2
Order By: Relevance
“…Autoantibodies can be present years before the onset of clinical symptoms 17. Transfer of human autoantibodies from patients with SLE can cause glomerulonephritis and proteinuria in murine experimental systems,18, 19 emphasizing that they can be pathogenic. Genome‐wide association studies (GWAS) have shown that over 80 loci can contribute to the risk of developing SLE 20.…”
Section: Slementioning
confidence: 99%
“…Autoantibodies can be present years before the onset of clinical symptoms 17. Transfer of human autoantibodies from patients with SLE can cause glomerulonephritis and proteinuria in murine experimental systems,18, 19 emphasizing that they can be pathogenic. Genome‐wide association studies (GWAS) have shown that over 80 loci can contribute to the risk of developing SLE 20.…”
Section: Slementioning
confidence: 99%
“…Several different antigenic cross-reactivities for anti-DNA antibodies have been identified (3). Recently, a pentapeptide with the sequence DWEYS (a molecular mimic of double-stranded DNA) was demonstrated to be present in the extracellular domain of murine and human N-methyl-D-asparate (NMDA) receptor subunits NR2a and NR2b (4). Furthermore, in patients with SLE, anti-DNA antibodies that cross-react with NR2 glutamate receptors have been shown to mediate apoptotic death of neurons in vivo and in vitro (5).…”
Section: Association Of Igg Anti-nr2 Glutamate Receptor Antibodies Inmentioning
confidence: 99%
“…These Abs are known to deposit in renal glomeruli, thereby contributing to lupus nephritis, as well as in skin and serosal membranes (13)(14)(15). We have previously demonstrated that a subset of these Abs cross-reacts with a 5-aa consensus sequence (D͞E W D͞E Y S͞G, or DWEYS for short) present in the NR2A and NR2B subunits of the NMDA receptor (NMDAR) (16,17).…”
mentioning
confidence: 99%